Implementation of Nationalism Values in Improving Student Character in Class IV PPKn Subjects - Zurriyati, Tia Husnul (Berpusi Publishing, 2023)
This research is motivated by the low value of nationalism in the character of fourth grade students at Al-Washliyah Ampera II Medan Private Elementary School in the academic year 2022/2023. The purpose of this study was to determine the implementation of nationalism values ​​can improve the character of students in class IV Al-Washliyah Ampera II Private Elementary School Medan. This type of research is classroom action research (CAR). And use the Qualitative method. In the pre-cycle it was known that the character of students in the Civics subject was in the low category, namely not having reached 75% so that the teacher and researchers intended to improve learning to implement nationalism values ​​in improving the character of students in class IV SD. Based on the results of a descriptive analysis of the student character in cycle I, the overall total score was 1946 with an average of 7.4.